(untitled) (Research, Society and Development, 2021)
It is noticed among students a certain lack of interest in Botany, that can be caused by “botanical blindness”, defined as the difficulty of perceiving the plants around you. One of the factors that contributes to this situation is the distance between what is taught at school and the student’s daily life. Thus, this work sought to analyze the use of native flora, of the region in which the school community is inserted, as a didactic tool that arouses this interest. To this end, diversified strategies were applied to students in the 2nd grade of high school at a school located in the municipality of Esperantina-PI. Studies on the vegetation of the municipality were searched in the literature. strategies were developed to associate these plants with themes of study of Botany. Data collection was performed using questionnaires with a qualitative and quantitative approach, seeking information about previous knowledge about Botany and the native flora of the region. The results obtained show that several activities with the use of flora increase the interest in the discipline. The students stated that they got to know more about Botany more generally, in addition, they stated to have more knowledge about native plants in the region.